The impact of IFRS adoption on audit fees: Evidence from Malaysian listed companies - Wan Lokman, Wan Abdul Wahid; Ab. Rashid, Hafiz Majdi; Annuar, Hairul Azlan (2013)
The purpose of this study is to examine the association between IFRS adoption (in the context of Malaysia, MASB aligns its standards substantially with the IFRS requirements and called the standards as FRS1) and audit fees paid to external auditors in Malaysia. Specifically it is argued that new accounting standards, FRS is perceived to have substantial differences from the old standards (i.e. MASB Standards), more complicated and thus require auditors to undertake greater audit efforts, which in turn lead to higher fees charged to clients. Furthermore, it is also hypothesised that higher audit fees are expected to be stronger for companies, which adopt FRS as these companies are being perceived to have higher risks. This is turn results in higher fees paid to the external auditors. This study employs multiple regression analysis. The data for the study is obtained from secondary data. The sample companies are 170 companies listed on Bursa Malaysia for the financial year ended 2006 (i.e. the first year which the MASB converged its standards to IFRS). Based on 170 sample firms, the results reveal that IFRS adoption is positively and significantly associated with statutory audit fees. The results are consistent with the literature which suggests IFRS adoption will result in increase scope of work and responsibility of the external auditors, which finally entails additional costs. The findings of this study in Malaysia offer support for previous finding on complexity of IFRS and lack of preparation in adoption among Malaysian companies. However, there is no evidence to support that non-audit fees are positively and significantly associated with IFRS adoption. This study contributes to the audit fees literature by examining the association between IFRS adoption and fees paid to external auditors. In particular, instead of using longitudinal study, this study focuses on the first year of IFRS adoption. Furthermore, this study is conducted in Malaysia, which is a unique environment that offers a different development toward IFRS adoption, whereby MASB gradually and progressively improve the accounting standards toward full IFRS adoption in year 2012.